Practices, Challenges, and Needs: Language Assessment Literacy among English Teachers in Islamic Secondary Schools - Indrasanti, Lutfi; Wita, Fitri Rahma (Jurusan Pendidikan Bahasa dan Seni FKIP Universitas Pattimura, 2022)
This study investigates English teachers’ Language Assessment Literacy (LAL) within Islamic secondary schools, focusing on MTs and MA Muhammadiyah Tanjung Bonai. In these contexts, teachers play a crucial role in evaluating students’ language abilities but often face limited formal training, scarce resources, and curricula dominated by written-test orientations. This research aims to describe teachers’ assessment practices, identify the challenges they face, and explore their professional development needs in LAL. Employing a qualitative multiple case study design, data were collected through semi-structured interviews with 4–6 English teachers and school principals, classroom observations, and document analysis of lesson plans, test instruments, rubrics, and assessment policies. Thematic analysis with source triangulation ensured validity. Findings reveal that teachers rely predominantly on traditional written assessments focusing on grammar and vocabulary, with limited understanding of communicative, valid, and reliable assessment principles. Key challenges include the absence of LAL-focused training, insufficient time for formative assessment, resource constraints, and tensions between national exam demands and communicative pedagogy. Despite this, teachers demonstrate growing awareness of authentic, performance-based assessment and feedback practices. The study highlights the unique Islamic school context, contributing novel insights into LAL in rural Indonesia and recommending context-sensitive professional development to enhance assessment competence and equity.